2018
DOI: 10.3389/fgene.2018.00614
|View full text |Cite
|
Sign up to set email alerts
|

Genome Assembly for a Yunnan-Guizhou Plateau “3E” Fish, Anabarilius grahami (Regan), and Its Evolutionary and Genetic Applications

Abstract: A Yunnan-Guizhou Plateau fish, the Kanglang white minnow (Anabarilius grahami), is a typical “3E” (Endangered, Endemic, and Economic) species in China. Its distribution is limited to Fuxian Lake, the nation’s second deepest lake, with a significant local economic value but a drastically declining wild population. This species has been evaluated as VU (Vulnerable) in the China Species Red List. As one of the “Four Famous Fish” in Yunnan province, the artificial breeding has been achieved since 2003. It has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 66 publications
3
24
1
Order By: Relevance
“…The ancestral state reconstruction uncovered some groups, especially those in some monophyletic putative subfamilies, and had similar values to the ancestral number of IBs, such as Hypophthalmichthyinae (109–118), Xenocyprinae (109–134), Leuciscinae (114–141), Cultrinae (119–139), and Gobiobotinae (105–113). For a controversial phylogenetic position of Tinca (see more details in Jiang et al, ), the number of IBs showed closer relationship to Acheilognathinae than to other Leuciscinae, which was consistent with the current phylogenetic relationship in Figure . Another interesting pattern was detected in Sinocyclocheilus , the total number of IBs, epineurals, and epipleurals was distinctly varied, and these typical cave fishes (troglobites) had fewer IBs than atypical cave species (troglophiles; terms according to Zhao, Gozlan, & Zhang, ).…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…The ancestral state reconstruction uncovered some groups, especially those in some monophyletic putative subfamilies, and had similar values to the ancestral number of IBs, such as Hypophthalmichthyinae (109–118), Xenocyprinae (109–134), Leuciscinae (114–141), Cultrinae (119–139), and Gobiobotinae (105–113). For a controversial phylogenetic position of Tinca (see more details in Jiang et al, ), the number of IBs showed closer relationship to Acheilognathinae than to other Leuciscinae, which was consistent with the current phylogenetic relationship in Figure . Another interesting pattern was detected in Sinocyclocheilus , the total number of IBs, epineurals, and epipleurals was distinctly varied, and these typical cave fishes (troglobites) had fewer IBs than atypical cave species (troglophiles; terms according to Zhao, Gozlan, & Zhang, ).…”
Section: Resultssupporting
confidence: 82%
“…The tree topology (Figure ) was largely consistent with most of the previous genetic studies derived from different DNA fragments (Wang et al, ; Yang, Sado, et al, ). The three major subclades (Clades I, II, and III) were also identical with those found by Jiang et al (), who provided a well‐resolved inter‐subfamily relationship of cyprinids at genome level (although the monophyly of each subfamily was beyond their aims for that paper). In this study, discussion of the deep phylogenetic relationship of the Cyprinidae is not our main focus; however, the tree we present here indicates that most of the morphological‐based subfamilies proposed by Chen () are not monophyletic groups (Figure ), thus implying this popular 12‐subfamily classification (Chen, ) needs to be revised.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Kanglang white minnow (KWM), Anabarilius grahami, is a typical fish species with "3E" (Endangered, Endemic, and Economic) status and priorities in the Yunnan-Guizhou Plateau of China [1]. It has been known as one of the "Four Famous Fishes" in Yunnan, with a restricted distribution in Fuxian Lake, the second deepest lake in China [2].…”
Section: Introductionmentioning
confidence: 99%